The role of ASPECTS score, atrial fibrillation, and revascularization therapy in predicting hemorrhagic transformation of ischemic stroke: results from a prospective cohort study - Elena Costru-Tasnic; Elena Costru-Tasnic; Mihail Gavriliuc; Mihail Gavriliuc; Olesea Odainic; Mihai Tasnic; Elena Manole (Frontiers in Neurology)
IntroductionHemorrhagic transformation (HT) can seriously complicate and worsen the clinical outcome of acute ischemic stroke (AIS) patients. Atrial fibrillation (AF), larger stroke volumes, and reperfusion therapy are associated with increased risk for HT in AIS. The aim of our research was to evaluate the combined prognostic value of the ASPECTS score, AF, and revascularization therapy in predicting HT in AIS patients.MethodsA prospective observational study was conducted. Demographic data, presence of AF, application of revascularization therapy, and baseline ASPECTS were recorded. The primary outcome was the occurrence of HT during hospitalization. Univariate and multivariate logistic regression analyses were applied to identify potential predictors. ROC analysis was performed to assess the prognostic value of the analyzed parameters for HT prediction.ResultsData from 150 successive AIS patients was registered for the final analysis. The active group (with HT during hospitalization) included 55 patients. No significant differences in age, gender distribution, or time to admission between the HT and control groups, were recorded. Lower ASPECTS, presence of AF, and revascularization therapy were independently associated with an increased risk of HT (p = 0.001, p = 0.004, and p = 0.007, respectively). ROC analysis for combined use of ASPECTS, AF, and revascularization therapies showed good predictive performance, AUC 76.51% (95% CI: 68.16–84.86%).ConclusionOur findings suggest that ASPECTS score, AF, and revascularization therapy are important predictors of hemorrhagic transformation in AIS. These results support the use of a combined clinical-imaging approach for risk stratification of HT in acute ischemic stroke patients.